Perbandingan klinik swasta di bandar dan luar bandar di Negeri Selangor, 2009 - Sharifa Ezat WP; Natrah MS; Khalib AL; Hasni H (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2009)
Introduction : Selangor’s private clinic registry system had been introduced in 2006 following gazettment of The Private Healthcare Facilities and Services Act. Through the act, data’s from the private clinics can be obtained and its characteristics can be compared between the urban and rural private clinic. An overview of the services can be known and an appropriate action can be planned. Methodology : A cross-sectional study was done on private clinics registered in state of Selangor. Using databased known as MedPCs (Medical Practice Control System), a purposive sampling was used to select four districts – two urban and two rural. All private clinics in the selected districts were studied and all details shall be collected on line. Result : District of Gombak and Klang were selected as urban and Sabak Bernam and Kuala Selangor represented rural area. Of a total 625 clinics selected, 90.0% (562) from urban and 10.0% (63) rural. Distributions of clinic were in line with the act. The most prominent services were general treatment (89.4%) and ability to serve more than eight hours daily (89.4%). Medical clinic still dominated at 84.0% compared to dentistry at 16.0%. About 70.6% were operated by male doctors. Though clinic services in rural were relatively as good as urban, the different were significantly observed to the ethnicity of the doctor. Indian doctors more in rural (46.03%), whilst in urban, Malay doctors were more dominant (39.50%). Followed closely by seniority, where rural doctors were much senior (51.02 years old), however, most of the doctors in rural private clinics experienced less exposure in government sectors, compared to those in urban areas. Conclusion : There were obvious difference in terms of distribution, where more clinics were located in urban compared to rural, but all were still in line to the act and their services were comparable. Most noticeable differences were ethnicity, seniority and past experience working in the public sector. Indian doctors were dominant in rural and Malay in urban. Although rural doctors were more senior, relatively they were less experienced working in the government sector.